A Comparative Evaluation of Xenograft, Platelet Rich Fibrin And Guided Tissue Regeneration Membrane In The Treatment Of Mandibular Grade II Furcation Defects - DR. P. VEERENDRA NATH REDDY , DR. K. PHANI YASASWINI , DR. CHAVVA LAKSHMI CHARAN REDDY , DR. B. LAVANYA , DR. C. SRILATHA , DR. P. BRAHMINI (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
One of the most exacting facets in therapy of periodontitis is the regeneration of periodontium affected by tooth furcation involvement. The furcation region has a complex anatomy that requires the use of specialized instruments called furcation curettes to treat it. Grade-II mandibular furcation defects are furthermore amenable to treatment and various techniques and materials have been employed to treat them with moderate success.AIM: The current study aimed to compare the surgical outcome of grade II furcation therapy with xenograft alone, xenograft along with GTR and xenograft along with PRF membrane.MATERIALS AND METHODS: This was a corresponding arm prospective randomized and interventional trial conducted within 18 different patients (27 defects) possessing Grade- II mandibular tooth furcation defects. The patients were spitted into three groups. In Group A, 6 patients with 9 defects have been treated by the positioning of Xenograft while in the Group B, 6 patients with 9 defects were treated by the positioning of Xenograft as graft and Guided Tissue Regeneration membrane while in Group C, 6 patients with 9 defects were treated by the positioning of Xenograft as graft and PRF as membrane. Clinical specifications including “Plaque Index (PI)”, “Probing Depth (PD)”, “Relative Vertical Clinical Attachment Level (RVCAL)”, “Relative Horizontal Clinical Attachment Level (RHCAL)”, and quantity of Bone fill by using CBCT, were approximated at baseline and Six months post-operatively. Differentiation between the groups was analyzed by employing ANNOVA test, whereas the paired t-test was used to analyse the mean values within the groups.RESULTS: On comparing those results between the groups it was observed that excepting from the Probing pocket depth (PD) and Depth of defect fill all other specifications were not arithmetically significant. The Probing depth  inbetween the groups at baseline (5.73±0.79) in Group-A, 6.18 ± 0.75 in Group B) and (6.09±0.70)  was not arithmetically significant, however after six months it was observed that in group A it was 1.73±0.79 , in the  group B 1.36±0.50 and in the group C 2.09± 0.70 which was arithmetically significant (p